Frontier review of the roles of exosomes in osteoarthritis. Issue 8 (17th June 2021) - Liu, Ding-Hao; Jheng, Ying-Chun; Chen, Po-Yin; Yarmishyn, Aliaksandr A.; Huang, Shih-En; Chien, Chian-Shiu; Tsai, Pin-Hsing; Chien, Yueh; Yang, Yi-Ping; Kao, Chung-Lan
Abstract : Osteoarthritis (OA) is a common degenerative disease; however, its exact pathophysiology and early diagnosis are still a challenge. Growing attention to the exosomes may inspire innovations that would make the current management of OA more effective. The exosomes in synovial fluid are relatively stable, and they can be easily isolated by the relatively noninvasive procedure of liquid biopsy to provide diagnostic and monitoring value. Some miRNAs (miR-504, miR-146a, miR-26a, miR-200c, and miR-210) have been known to be secreted in exosomes of OA patients. On the other hand, intraarticular injection of platelet-rich plasma (PRP) is becoming a popular therapy for OA patients. PRP is also a source of exosomes and their numerous contents. It is evident from the literature that PRP-derived exosomes can induce chondrogenic gene expression in OA chondrocytes. Here, we review the latest findings on the roles of exosomes in OA with the emphasis on PRP-derived exosomes and their potential applications for treating OA.